Behçet disease associated with gastrointestinal amyloidosis manifested as hematochezia: A case report. Issue 26 (June 2018) - Sato, Shuzo; Yashiro, Makiko; Matsuoka, Naoki; Kawana, Satoshi; Asano, Tomoyuki; Kobayashi, Hiroko; Tasaki, Kazuhiro; Watanabe, Hiroshi; Hashimoto, Yuko; Migita, Kiyoshi
Abstract: Rationale: Behçet disease (BD) is an inflammatory disorder characterized by recurrent oral aphthous ulcers, genital ulcers, ocular lesions, and skin lesions. Complication of amyloidosis in patients with BD is rare. Here, we report a case of BD with immunoglobulin light chain (AL)-amyloidosis manifested as hematochezia. Patient concerns: A 61-year-old man developed sudden hematochezia due to bleeding from multiple small colonic ulcers; AL-amyloid deposition was found on immunohistochemical examination of biopsy specimen of colonic ulcer. Systemic investigation revealed cardiac disfunction with cardiomegaly and progressive renal dysfunction, which indicated the presence of systemic AL-amyloidosis. Diagnoses: Based on the findings of colonic ulcers with cardiac and renal involvement, a diagnosis of systemic AL-amyloidosis complicated by incomplete BD was established. Interventions: He was treated with increased dose of oral prednisolone (20 mg/day), colchicine and mesalazine, because he was reluctant to receive aggressive chemotherapy (melphalan and dexamethasone) or autologous stem cell transplantation. Outcomes: Colonic ulcers completely diminished after treatment, however, he died because of severe urinary tract infection and progressive renal failure after one year of gastrointestinal (GI) manifestations. Lessons: Our case shows that patients with BD may have GI manifestations due not only to entero-BD but also due to GI amyloidosis.